Transcriptomics insights into the functional role of tick Ixodes ricinus proteins metalloprotease and antigen p23 - Rita Vaz-Rodrigues; Vincent C. Duru; Ard M. Nijhof; José de la Fuente (PLoS ONE, 2025)
Ixodes ricinus ticks (Acari: Ixodidae) are hematophagous ectoparasites and a major European vector of zoonotic diseases affecting global health. Tick salivary and midgut proteins antigen p23 (A0A0K8RKR7) and metalloprotease (A0A0K8RCY8) were previously implicated in the pathophysiology of the tick-borne allergy alpha-Gal syndrome (AGS). This study aimed to functionally characterize these two biomolecules, focusing on their role in I. ricinus tick feeding and reproduction through gene knockdown by RNA interference and midgut transcriptomic analysis. Validation of RNA-seq data was conducted using RT-qPCR analysis on tick midgut and salivary gland tissues. Silencing the expression of p23 and metalloprotease did not result in any significant differences in tick engorgement and egg batch weights compared to the control group. Gene set enrichment analysis following antigen p23 gene knockdown identified significantly upregulated pathways associated with protein production and suppressed routes mostly correlated with ion transport, lipid metabolism, catalytic activity, protein modification, and G-protein activity. Partial knockdown of the metalloprotease led to the upregulation of several biological and functional pathways associated with RNA splicing and significantly suppressed routes connected with detoxification, protein modification, catalytic activity and molecule binding. Antigen p23 appears to play a functional role in tick midgut cell homeostasis, primarily by participating in regulatory and signaling processes essential for cell viability. Metalloprotease is potentially involved in regulating midgut response to oxidative stress, thereby reducing tissue damage and promoting regular cell proliferation, growth and behavior. These results provide insights into tick physiology and bases for further research on tick-host interactions and AGS pathogenesis.